A landscape in transition : architecture for an extreme climatic condition : accommodating the informal within a flood-prone area - Edwards, John (School of Architecture, Planning and Geomatics, 2024)
[Not copying properly]Changing landscapes The npid urbanization !leen within the City of Cape-Town is a dyn2mic fluid, non-linor process as opposed to being stable or closely pcc:dicrJ.ble. Ecology and systems theory are· concepts inherent to the city and iu relationship with landSCllpe. Conceptualizing urbanization, human security and disaster risk, especially within Africa. will help unravel the issue at hand. The nature of the problem and the extreme conditions of flooding will also be explored. There are indiations that South A frica's climate is becoming increasingly variable (Napier & Rubin; 2002). Climate change increases the uncertainty fa.ced by vulnerable communities through a widening range of future climate variations and ha.z:trds. This is not a hypothetic:tl risk to be addressed §eVtral deades into the future, but a real increase in risk that is presently threatening livelihoods. (UNISDR; 2002) Residents of informal settlements in the Western Cape. as well as elsewhere in South Africa, are the hardest hit by extreme weather conditions and associated flooding. Thousands of households in the province and beyond suffer severe losses in informal dwelling floods and fires. During floods and fires. poor families suffer significant development setbacks. These disasters are also costly for the affected municipalities and provincial departments, and divert resources from other urgently needed services. (Holloway; 2007) rapid migration into the province and natural population growth have increased the number of informal settlements across the province. '('i.thin Cape Town alone, by 2007. mott than 220 separate informal settlements had been identified and mapped. (Holloway; 2007)